2001
DOI: 10.1128/aem.67.9.4353-4357.2001
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Mineralization of Stable-Isotope-Labeled 2-Methylnaphthalene

Abstract: An active sulfate-reducing consortium that degrades 2-methylnaphthalene (2-MNAP) at rates of up to 25 M day ؊1 was established. Degradation was inhibited in the presence of molybdate and ceased in the absence of sulfate. As much as 87% of 2-[ 14 C]MNAP was mineralized to 14 CO 2 . 2-Naphthoic acid (2-NA) was detected as a metabolite, and incubation with either deuterated 2-MNAP or [13 C]bicarbonate indicates that 2-NA is the result of oxidation of the methyl group. Also detected were carboxylated 2-MNAPs, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 17 publications
4
57
0
1
Order By: Relevance
“…In cases where PAHs were activated by other mechanisms and subsequently metabolized, no label was found in carboxylated metabolites after incubation with 13 C-bicarbonate. For instance, 2-methylnapthalene-degrading enrichments produced 2-naphthoic acid, but did not incorporate 13 C in the carboxyl group of the metabolite when incubated with labeled bicarbonate (Sullivan et al, 2001). Similarly, a sulfidogenic consortium capable of benzene mineralization did not incorporate 13 Ccarbon in the carboxyl group of benzoate when the cells were supplemented with 13 C-bicarbonate, suggesting that the carboxyl group in the metabolite was not a product of direct carboxylation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where PAHs were activated by other mechanisms and subsequently metabolized, no label was found in carboxylated metabolites after incubation with 13 C-bicarbonate. For instance, 2-methylnapthalene-degrading enrichments produced 2-naphthoic acid, but did not incorporate 13 C in the carboxyl group of the metabolite when incubated with labeled bicarbonate (Sullivan et al, 2001). Similarly, a sulfidogenic consortium capable of benzene mineralization did not incorporate 13 Ccarbon in the carboxyl group of benzoate when the cells were supplemented with 13 C-bicarbonate, suggesting that the carboxyl group in the metabolite was not a product of direct carboxylation .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first determination of the 16S rRNA sequence phylogeny of a sulfate-reducing phenanthrene-degrading culture. To date, two possible mechanisms for anaerobic PAH activation have been reported, with most work focused on the metabolism of two-ring compounds such as naphthalene and 2-methylnaphthalene (Sullivan et al, 2001;Annweiler et al, 2000Annweiler et al, , 2002. Only one study has helped clarify the metabolism of phenanthrene (Zhang and Young, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…3 c). A pathway producing carboxylated 2-methylnaphthalene has been suggested [Sullivan et al, 2001] but not fully deduced (not shown). However, analogous to the differential susceptibility of xylene isomers, considerably more experimentation will be required to elucidate the biodegradability of 1-methylnaphthalene and its potential metabolites, as its degradation is not simply analogous to the more susceptible isomer 2-methylnaphthalene.…”
Section: Alkyl-pahs: 2-methylnaphthalene and 1-methylnaphthalenementioning
confidence: 99%
“…They proved to be useful tools for examining the initial mechanisms of attack on compounds such as benzene, naphthalene, and phenanthrene and alkane degradation by strain AK-01 (30,38,39,48,49). In this report, we present the results of an investigation of the initial reactions of alkane degradation by strain Hxd3.…”
mentioning
confidence: 99%